2002
DOI: 10.1074/jbc.m200955200
|View full text |Cite
|
Sign up to set email alerts
|

The Human SNF5/INI1 Protein Facilitates the Function of the Growth Arrest and DNA Damage-inducible Protein (GADD34) and Modulates GADD34-bound Protein Phosphatase-1 Activity

Abstract: The growth arrest and DNA damage-inducible protein (GADD34) mediates growth arrest and apoptosis in response to DNA damage, negative growth signals, and protein malfolding. GADD34 binds to protein phosphatase-1 (PP1) and can attenuate translational elongation of key transcriptional factors through dephosphorylation of eukaryotic initiation factor-2␣. We reported previously that the human trithorax leukemia fusion protein (HRX) can bind to GADD34 and abrogate GADD34-mediated apoptosis in response to UV irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 58 publications
1
40
0
1
Order By: Relevance
“…This does not rule out the effects of viral homology deletions on other parameters such as transformation, and complex effects such as tumor formation and angiogenesis in whole animals. Recently, it was shown that binding of Gadd34 to SNF5 was required for Gadd34-mediated growth suppression since Gadd34 mutations that prevented SNF5 binding also prevented growth suppression (Wu et al, 2002). SNF5 binding was shown to be nearer the carboxyl end of Gadd34 (see Figure 4), suggesting that SNF5 may permit Gadd34-mediated growth suppression through exlusion of other Gadd34-binding proteins whose binding to Gadd34 prevents these effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This does not rule out the effects of viral homology deletions on other parameters such as transformation, and complex effects such as tumor formation and angiogenesis in whole animals. Recently, it was shown that binding of Gadd34 to SNF5 was required for Gadd34-mediated growth suppression since Gadd34 mutations that prevented SNF5 binding also prevented growth suppression (Wu et al, 2002). SNF5 binding was shown to be nearer the carboxyl end of Gadd34 (see Figure 4), suggesting that SNF5 may permit Gadd34-mediated growth suppression through exlusion of other Gadd34-binding proteins whose binding to Gadd34 prevents these effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PP1, Snf5, Lyn kinase and HRXbinding domains have all been mapped to this region of Gadd34 (Figure 4), and interaction of Gadd34 with these proteins has been reported to be necessary for Gadd34-mediated growth suppression and apoptosis (Adler et al, 1999;Grishin et al, 2001;Novoa et al, 2001;Wu et al, 2002). In addition, HRX, G34BP, GaHSP40 and Translin all bind the carboxyl half of the protein, which includes the region missing in PEG-3 (Adler et al, 1999;Isobe, 1999, 2000;Hasegawa et al, 2000a, b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatidyl inositol 4,5-bisphosphate is also involved in the activation of the serine/ threonine kinase Akt, by recruiting it to the plasma membrane, where it is activated via phosphorylation. In addition, INI1 was recently shown to interact with the catalytic subunit of protein phosphatase 1 (Wu et al, 2002), which has a multitude of substrates, including Akt (Xu et al, 2003). These observations led us to question whether a potential relationship also existed between Akt and the hSWI/SNF complex.…”
Section: Introductionmentioning
confidence: 99%
“…6). Similarly, PP1 was identified as a component of another chromatin-remodeling complex, which also contains the PP1 interactor GADD34 and the SNF5 protein (43). GADD34 is a stress-induced protein that facilitates cell-cycle arrest, whereas SNF5 is a component of a SWI/SNF chromatin remodeling complex that acts by repositioning nucleosomes.…”
Section: Mechanism Of Transcriptional Repression By Nipp1-mentioning
confidence: 99%